Determination of optimum model of tactical preparation for training process control in regbilig - Velor Mesitsky; Arthur Martirosyan; Oleg Podolyaka (Kharkiv State Academy of Physical Culture, 2014)
Purpose: determination of the optimal model of tactical training for management training process in regbilig. Material and research methods: 34 sportsmen of cities of Simferopol and Sevastopol, participant of championship of Ukraine, took part in research, from regbilig among grown man commands. Results: presented the optimum model of tactical preparation for control training process in regbilig. Conclusions: first optimum tactical model descriptions, developed on the basis of deep analysis of appearances of the best commands of the world, Superligi of England, are examined in Ukraine, NRL of Australia, which allow deeper to give a glance on preparation of command which does possible to apply these base charts in all periods of preparation of command on the whole, taking into account the necessary level of development of physical qualities and technical preparedness of rugby-players. It allows it is more optimum to manage an training process in preparation, both in junior commands and in the commands of masters.